IL-10 Accelerates Re-Endothelialization and Inhibits Post-Injury Intimal Hyperplasia following Carotid Artery Denudation. - Suresh K Verma; Venkata Naga Srikanth Garikipati; Prasanna Krishnamurthy; Mohsin Khan; Tina Thorne; Gangjian Qin; Douglas W Losordo; Raj Kishore (PLoS ONE, 2016)
The role of inflammation on atherosclerosis and restenosis is well established. Restenosis is thought to be a complex response to injury, which includes early thrombus formation, acute inflammation and neo-intimal growth. Inflammatory cells are likely contributors in the host response to vascular injury, via cytokines and chemokines secretion, including TNF-alpha (TNF). We have previously shown that IL-10 inhibits TNF and other inflammatory mediators produced in response to cardiovascular injuries. The specific effect of IL-10 on endothelial cell (ECs) biology is not well elucidated. Here we report that in a mouse model of carotid denudation, IL-10 knock-out mice (IL-10KO) displayed significantly delayed Re-endothelialization and enhanced neo-intimal growth compared to their WT counterparts. Exogenous recombinant IL-10 treatment dramatically blunted the neo-intimal thickening while significantly accelerating the recovery of the injured endothelium in WT mice. In vitro, IL-10 inhibited negative effects of TNF on ECs proliferation, ECs cell cycle, ECs-monocyte adhesion and ECs apoptosis. Furthermore, IL-10 treatment attenuated TNF-induced smooth muscle cells proliferation. Our data suggest that IL-10 differentially regulate endothelial and vascular smooth cells proliferation and function and thus inhibits neo-intimal hyperplasia. Thus, these results may provide insights necessary to develop new therapeutic strategies to limit vascular restenosis during percutaneous coronary intervention (PCI) in the clinics.